A Comparison of Learners’ Affect and Behaviors While Using an Intelligent Tutor and an Educational Game - Rodrigo, Ma. Mercedes T (Archīum Ateneo, 2009)
We compared the extent to which of students exhibit certain affect states and behaviors while using an intelligent tutoring system, Aplusix, and an educational game, Math Blaster 9-11. We found that students using Math Blaster showed more boredom and less flow than the students who used Aplusix. Despite exhibiting less flow, students using the game spent more time ontask and less time in conversation or in gaming the system (defined as hint abuse or systematic guessing) that those using Aplusix. We were able to associate affective states with certain behaviors. We found that, in Aplusix, gaming the system tended to co-occur with boredom and confusion. In both Aplusix and Math Blaster, confusion and delight tended to dampen on-task behavior but foster on-task conversation. Also in both cases, flow was associated with on-task behavior and is not associated with off-task behaviors. Findings from this study suggest that, regardless of software format, boredom is an undesirable affective state. Flow is clearly desirable. Confusion and delight reduce solitary on-task behavior yet foster greater communication with teachers or classmates. The findings also provide some evidence that, regardless of the affective states they evoke, game formats tend to keep students on-task.